2000
DOI: 10.3354/meps200077
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of benthic microalgae, phytoplankton and the detritus of smooth cordgrass Spartina alterniflora and the common reed Phragmites australis to brackish-marsh food webs

Abstract: We conducted a study to determine the trophic pathways leading to juvenile fish in 2 mesohaline tidal marshes bordering Delaware Bay. The relative roles of the major primary producers in supplying energy, ultimately, to the mummichog Fundulus heteroclitus were assessed by measuring the stable isotopic compositions of juveniles (21 to 56 mm total length, TL; most of which were young-of-the-year) and those of macrophyte vegetation, phytoplankton, and benthlc microalgae at each site. We collected samples of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 50 publications
8
95
0
1
Order By: Relevance
“…Other authors have found that fish species composition was also not affected by common reed invasion (Meyer et al, 2001) or that nekton densities are similar to those in some non-P. australis dominated wetlands (Hanson et al, 2002). Moreover, Wainright et al (2000) provided evidence that P. australis may contribute to the food chain in tidal marsh systems. Other studies showed differences, such as Posey et al (2003), who reported a slightly higher abundance of fauna in Spartina alterniflora marshes than in P. australis marshes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other authors have found that fish species composition was also not affected by common reed invasion (Meyer et al, 2001) or that nekton densities are similar to those in some non-P. australis dominated wetlands (Hanson et al, 2002). Moreover, Wainright et al (2000) provided evidence that P. australis may contribute to the food chain in tidal marsh systems. Other studies showed differences, such as Posey et al (2003), who reported a slightly higher abundance of fauna in Spartina alterniflora marshes than in P. australis marshes.…”
Section: Discussionmentioning
confidence: 75%
“…Several functions of the salt marshes may therefore be modified by such an invasion: the export capacity of the salt marsh could be modified and in turn could affect mussel and oyster culture with resulting economic effects; the habitat value for Anatidae and other game birds could be changed Valéry et al, 2004). The role of invasive plants on the alteration of trophic function for larvae and juveniles of fish and crustaceans has been studied along the North American Atlantic coast with common reed Phragmites australis (see for example Able and Hagan, 2000;Wainright et al, 2000;Hanson et al, 2002). In comparison, the effects of E. athericus on trophic function for European fish have rarely been studied, although European salt marshes play important roles for fish communities.…”
Section: Introductionmentioning
confidence: 99%
“…This higher abundance of infauna adjacent to natural marsh habitats as compared to anthropogenically altered shorelines also occurs in the York and Elizabeth-Lafayette Rivers (Seitz et al, 2006). This is most likely driven by differences in allochthonous carbon inputs between the marshes and the hardened shorelines (Quan et al, 2007;Roman and Daiber, 1989;Seitz et al, 2006;Wainright et al, 2000), though differences in water flow (which we did not measure) may also have contributed (Seitz et al, 2006). Additionally, bulkheads are often made of CCA-treated wood, which can have a negative effect on benthic organisms (Weis et al, 1998); however, in this system, riprap, not bulkheads, had the lowest density of benthic macrofauna, and its benthic community differed more from the marshes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of bulkheads, this may be due to toxic chemicals leaching from treated lumber (Weis et al, 1998). However, because marshes can supply substantial amounts of allochthonous carbon to subtidal habitats (Quan et al, 2007;Roman and Daiber, 1989;Wainright et al, 2000), replacing them with riprap or bulkheads, which cannot supply such resources, may lower macrofaunal densities (Seitz et al, 2006). Additionally, hardened shorelines are frequently associated with lower densities and smaller sizes of nektonic species Peterson et al, 2000), though not in all cases (Seitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 8 (Peterson et al 1986;Sullivan & Moncreiff 1990;Currin et al 1995;Wainright et al 2000). The 8 13 C signatures of MPB were more depleted at the highshore location than at the mid-shore location of both sites in March.…”
Section: Stable Isotope Signatures Of Food Sourcesmentioning
confidence: 99%